2021
DOI: 10.3390/math9020143
|View full text |Cite
|
Sign up to set email alerts
|

Grid Frequency and Amplitude Control Using DFIG Wind Turbines in a Smart Grid

Abstract: Wind-generated energy is a fast-growing source of renewable energy use across the world. A dual-feed induction machine (DFIM) employed in wind generators provides active and reactive, dynamic and static energy support. In this document, the droop control system will be applied to adjust the amplitude and frequency of the grid following the guidelines established for the utility’s smart network supervisor. The wind generator will work with a maximum deloaded power curve, and depending on the reserved active pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
4
0
1
Order By: Relevance
“…Coefficients c 1 to c 6 depend on the wind turbine under study. The authors in [27] show a similar expression with numerical coefficients based on a model found in Matlab/Simulink. A review of mathematical models of the coefficient of performance as a function of TSR and pitch angle can be found in [28].…”
Section: General Concepts About Harnessing Wind Energysupporting
confidence: 58%
See 1 more Smart Citation
“…Coefficients c 1 to c 6 depend on the wind turbine under study. The authors in [27] show a similar expression with numerical coefficients based on a model found in Matlab/Simulink. A review of mathematical models of the coefficient of performance as a function of TSR and pitch angle can be found in [28].…”
Section: General Concepts About Harnessing Wind Energysupporting
confidence: 58%
“…FOC, also known as vector control, sets a two-dimensional rotating reference, called d-q, whose direct axis is usually aligned with the stator magnetic flux. Under this scheme, the torque and the active power are proportional to the q-axis component of the rotor current, whereas the q-axis component is used to regulate the reactive power flow [27,40,[44][45][46][47][48][49][50][51][52][53][54][55][56]. Figure 10 depicts the control of a DFIG with some of the additional controllers discussed in this article.…”
Section: Variable-speed Wind Turbinesmentioning
confidence: 99%
“…However, the asynchronous generator is the most widely used in the field of electric power generation using wind energy, especially in the case of variable wind speed. This is due to the advantages and characteristics of the asynchronous generator such as ease of control, efficiency, durability, and low cost [5].…”
Section: Introductionmentioning
confidence: 99%
“…The classical control schemes for the RSC have been derived from the established schemes used for adjustable motor drives. Typically, they are current controlled [7], where the set-points of the current controllers are derived from the references for active/reactive power, torque or voltage magnitudes [8,9]. The current control is usually done in a rotating reference frame.…”
Section: Introductionmentioning
confidence: 99%